Effect of Astaxanthin on Cataract Formation Induced by Glucocorticoids in the Chick Embryo. (10th July 2014) - Ishikawa, Sayano; Hashizume, Kouhei; Nishigori, Hideo; Tezuka, Yu; Sanbe, Atsushi; Kurosaka, Daijiro
Abstract: Purpose : To examine whether astaxanthin (AST) prevent the cataract formation induced by glucocorticoid in chick embryo. Materials and methods : Hydrocortisone hemisuccinate sodium (HC) (0.5 μmol/egg) was administered directly into the air chamber in the egg shell of chick embryo day 15. The eggs were then kept in an incubator at same conditions and administered 100 μL of 50 (HC + AST50 group), 80 (HC + AST80 group), 100 (HC + AST100 group) mg/mL of AST solutions dissolved in dimethyl sulfoxide (DMSO) 3 h after administration of HC. In addition, non-HC treated group (treated with physiological saline without HC and 100 μL of DMSO), HC-alone group (treated with 0.5 μmol of HC and 100 μL of DMSO), and AST100 group (treated with physiological saline without HC and 100 μL of DMSO) were also incorporated. After 48 h of treatment, lenses were removed from embryo and classified into five stages according to developed opacity. The amounts of reduced glutathione in the lenses and the blood glucose levels were measured. Results : The average scores of lens opacitiy were 2.63 ± 1.02 nmol/lens (HC-alone), 2.78 ± 0.97 nmol/lens (HC + AST50), 2.22 ± 1.20 nmol/lens (HC + AST80) and 1.84 ± 0.83 nmol/lens (HC + AST100; p  < 0.05), respectively. Administration of AST decreased the lens opacity dose-dependently. The amounts of reduced glutathione in lenses were 11.6 ± 2.8 nmol/lens (HC-alone), 11.3 ± 2.7 nmol/lens (HC + AST50), 13.4 ± 2.4 nmol/lens (HC + AST80) and 13.7 ± 3.1 nmol/lens (HC + AST100; p  < 0.05), respectively. Higher levels of AST prevented loss of reduced glutathione from the lens. Conclusion : These findings support that AST protects glucocorticoid-induced cataract in chick embryo.